Blood Profile of Vitamin A and β-Carotene During Post-Partum Period in Surti Goats - Manat, Tanvi D.; Chaudhary, Sandhya S.; Singh , Virendra Kumar; Patel , Sanjay B. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The present study was undertaken to study levels of vitamin A and β-carotene in blood of post partum Surti goats. 40 Surti goats were selected comprising of 20 goats with recent parturition (treatment group) and 20 non-pregnant animals (control group). Blood collection was done on 0, 7, 14, 21, 30 and 45 day post-kidding (treatment group) and once from control group and analyzed for Vitamin A and β-carotene. Both the analytes were significantly low on 0 day. Significant difference (P<0.05) in vitamin A as well as β-carotene (P<0.01) was observed between 0 and 21st day post partum followed by non-significant difference in vitamin A after 21 days. However, β-carotene values at 21st day significantly differed from those at 30th and 45th day. Non–significant difference between control and treatment group from 7th day onwards was observed in vitamin A. β-carotene values of treatment group were significantly lower at 0 and 21st day postpartum as compared to control. It was concluded that on the day of kidding there is decrease in circulatory levels of vitamin A and β-carotene and this decrease can be used as an indicator of stress.